Did Patagonia collide with Gondwana in the Late Paleozoic? Some insights from a multidisciplinary study of magmatic units of the North Patagonian Massif - A.E. RAPALINI; M.G. LÓPEZ DE LUCHI; C. MARTÍNEZ DOPICO; F.G. LINCE KLINGER; M.E. GIMÉNEZ; PATRICIA MARTÍNEZ (Geologica Acta, 2011)
The origin of Patagonia and its relations with the South American crustal blocks to the north have been a matter of debate for decades. We report results from a multidisciplinary study centered on Paleozoic granitoids exposed in the northeastern corner of the North Patagonian Massif. Microstructural and magnetofabric studies reveal two suites of granitoids. Late Carboniferous (?) granitoids (Yaminué Complex, Tardugno Granodiorite, Cabeza de Vaca leucogranite) were emplaced and subsequently deformed in a major NNE-SSW compressive stress regime that also provoked top-to-the-SW thrust deformation in shallow crustal levels. Gravity and geobarometric studies show that the same major deformation event has been recorded at different crustal levels. The age and type of deformation of this event recorded across the northern boundary of Patagonia strongly supports a Late Carboniferous – Early Permian frontal collision between Patagonia and Gondwana. This major deformation event ceased by 281 Ma when the Navarrete Plutonic Complex, which shows mainly magmatic fabrics, was emplaced under a far-field WNW-ESE stress regime. Crustal continuity between the North Patagonian Massif and the Pampia and Arequipa- Antofalla terranes is suggested by similar Late Paleoproterozoic crustal model ages, comparable detrital zircon ages in Early Paleozoic successions, the apparent continuity of an Early Ordovician continental magmatic arc and paleomagnetic data. Reconciliation of this evidence with the Late Paleozoic frontal collision is obtained in a tectonic model that suggests that the North Patagonian Massif is a parautochthonous crustal block.